Unlocking the Therapeutic Potential of Avocado Peel Waste: A Comprehensive Review of Phytochemicals and Pharmacological Activities - Awidarta, Kevin; Rohman, Abdul; Nugroho, Agung Endro (Journal of Food and Pharmaceutical Sciences, 2025)
Avocado peel waste, a significant byproduct of the global avocado industry, represents an underutilized resource rich in bioactive compounds, prompting growing interest in its potential pharmacological applications. This review addresses the need to explore these compounds within the context of sustainable waste management and natural therapeutic development, aiming to evaluate their chemical composition and biological activities. A comprehensive analysis was conducted by synthesizing data from peer-reviewed studies, focusing on phytochemical identification using advanced techniques such as UHPLC-QTOF-MS, HPLC-DAD, and LC-DAD-ESI-MS, alongside pharmacological assessments via methods like DPPH, TBARS, and in vitro assays. The findings reveal that avocado peels, particularly from the Hass cultivar, contain diverse phytochemicals including phenolics, flavonoids, and organic acids, exhibiting antioxidant, neuroprotective, antibacterial, antifungal, antiplatelet, antiaging, anti-inflammatory, and anticancer properties. These activities are attributed to mechanisms such as radical scavenging, enzyme inhibition, and apoptosis induction, with specific studies highlighting neuroprotective effects in Parkinson’s disease models. The review concludes that avocado peel waste holds substantial promise as a sustainable source of bioactive compounds for food and pharmaceutical applications, though challenges like bioavailability and cultivar variability necessitate further research. Innovative extraction and formulation strategies could unlock its full therapeutic potential, contributing to a circular economy and health innovation.